Klasifikasi Tanah Lempung Berdasarkan Sistem Uscs (Unified Soil Classification System) Dan Aashto (American Association of State Highway and Transportation Officials) - Sabilla, Arissa; Hildayani, Cut Sitti Rafidatul (Universitas Iskandar Muda, 2025)
The fine-grained soil in the Gampong Keutapang Quarry area, Lhoong District, is widely used as embankment material and construction base soil, but to date there is no documented geotechnical characteristic data. This condition poses a risk of construction failure due to the incompatibility of the soil type with its intended use. Therefore, this study aims to identify the physical properties of the clay soil at the location and determine its classification using two international standard systems, namely USCS and AASHTO. The research method uses a quantitative experimental approach through a series of laboratory tests, including the determination of natural water content, specific gravity, sieve analysis, and Atterberg limit tests. The test results show that the soil has an average water content of 39.98%, a specific gravity of 2.619 g/cm³, a liquid limit (LL) of 64.24%, a plastic limit (PL) of 39.98%, and a plasticity index (PI) of 24.25%. The high LL and PI values ​​cause the soil to be classified as MH in the USCS system, namely inorganic silt with high plasticity. Meanwhile, based on the AASHTO system, LL values ​​> 40% and PI > 11% place the soil in the A-7-5/A-7-6 group, indicating subgrade quality with low bearing capacity. The results of this study provide important contributions to the field of geotechnics, particularly in providing baseline information for more sustainable construction planning and infrastructure development.